Step
*
1
of Lemma
derivative-function-rminus
.....antecedent..... 
1. f : ℝ ⟶ ℝ
2. f' : ℝ ⟶ ℝ
3. ∀x,y:ℝ.  ((x = y) 
⇒ (f'[x] = f'[y]))
4. d(f[x])/dx = λx.f'[x] on (-∞, ∞)
⊢ d(-(x))/dx = λx.-(r1) on (-∞, ∞)
BY
{ (ProveDerivative THEN Auto) }
Latex:
Latex:
.....antecedent..... 
1.  f  :  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
2.  f'  :  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
3.  \mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  (f'[x]  =  f'[y]))
4.  d(f[x])/dx  =  \mlambda{}x.f'[x]  on  (-\minfty{},  \minfty{})
\mvdash{}  d(-(x))/dx  =  \mlambda{}x.-(r1)  on  (-\minfty{},  \minfty{})
By
Latex:
(ProveDerivative  THEN  Auto)
Home
Index